The Effect of Financial Technology Implementation and Employee Digital Literacy Levels on the Accounting Information System at Bank Papua, South Sulawesi Branch - Cathalina, Chintya; Toratu, Xenia Vincensia; Sambara, Ratu; Paranoan, Natalia; Daud, Maiercherinra (Journal of Development Research, 2025)
This study analyzes the effect of Financial Technology (fintech) implementation and employees’ digital literacy levels on the Accounting Information System at Bank Papua, South Sulawesi Branch. A quantitative approach was employed using a survey of 36 respondents who are directly involved in operating the accounting information system. The data were analyzed using multiple linear regression to examine both partial and simultaneous influences among the variables. The results indicate that fintech implementation and employees’ digital literacy levels have a positive and significant effect on the accounting information system, both partially and simultaneously. The combined contribution of the two variables reached 74.3%, suggesting that the effectiveness of fintech implementation is strongly influenced by employees’ digital literacy. These findings highlight the importance of enhancing digital competencies among human resources to optimize the performance of modern accounting information systems in the banking sector.